STATISTICAL EQUILIBRIUM OF THE LITHIUM IN DIFFERENT METALLICITY DWARF ATMOSPHERES WITH Teff = 5770 K, lg g = 4.44 - Pavlenko, Ya. V.; Yakovina, L. A. (Одеські астрономічні публікації, 2017)
Results of computations of the lithium statistical equilibrium in atmospheres of Teff = 6270, 5770, 5270 and lg g = 4.44 dwarfs of metallicities [μ] = -0, - 1, - 2, - 3 are discussed. It is shown that NLTE corrections are less then 0.1 dex for abundances of lithium observed in these stars.